Development and Validation of a Radiomics Nomogram for Predicting Clinically Significant Prostate Cancer in PI-RADS 3 Lesions - Li, Tianping; Sun, Linna; Li, Qinghe; Luo, Xunrong; Luo, Mingfang; Xie, Haizhu; Wang, Peiyuan (Frontiers in Oncology, 2022)
Purpose: To develop and validate a radiomics nomogram for prediction of clinically significant prostate cancer (CsPCa) in Prostate Imaging-Reporting and Data System (PI-RADS) category 3 lesions. Methods: We retrospectively enrolled 306 patients within PI-RADS 3 lesion from January 2015 to July 2020 in institution 1, the enrolled patients were randomly divided into training group (n = 199) and test group (n = 107). Radiomics features were extracted from T2-weighted imaging (T2WI), apparent-diffusion coefficient (ADC) imaging, and dynamic contrast-enhanced (DCE) imaging. Synthetic minority oversampling technique (SMOTE) was used to address class imbalance. The ANOVA analysis and LASSO regression model were used for feature selection and radiomics signature building. Then, a radiomics score (Rad-score) was acquired. Combined with serum prostate-specific antigen density (PSAD) level, a multivariate logistic regression analysis was used to construct a radiomics nomogram. Receiver operating characteristic curve analysis (ROC) was used to evaluate radiomics signature and nomogram. The radiomics nomogram calibration and clinical usefulness were estimated through calibration curve and decision curve analysis (DCA). External validation was assessed, an independent validation cohort contained 65 patients within PI-RADS 3 lesion from January 2020 to July 2021 in institution 2. Results: A total of 75 (24.5%) and 16 (24.6%) patients had CsPCa in institution 1 and 2, respectively. The radiomics signature with SMOTE augmentation method had a higher area under the ROC curve (AUC) [0.840, (95% CI, 0.776-0.904)] than that without SMOTE method [0.730 (95% CI, 0.624-0.836), P = 0.08] in the test group, and significantly increased in the external validation group [0.834 (95% CI, 0.709-0.959) vs. 0.718 (95% CI, 0.562-0.874), P = 0.017]. The radiomics nomogram showed good discrimination and calibration, with an AUC of 0.939 (95% CI, 0.913-0.965), 0.884 (95% CI, 0.831-0.937), and 0.907 (95% CI, 0.814-1) in the training, test, and external validation group, respectively. The DCA demonstrated the clinically useful of radiomics nomogram. Conclusion: The radiomics nomogram that incorporates the MRI-based radiomics signature and PSAD, can be conveniently used to individually predict CsPCa in patients within PI-RADS 3 lesion.